2020
DOI: 10.1109/access.2020.2997777
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Extra Train Paths Into Cyclic Timetable Based on the Genetic Algorithm

Abstract: In order to support the process of scheduling a hybrid cyclic timetable, this paper is devoted to inserting additional non-cyclic train paths into existing cyclic timetable. The adding train paths problem is an integration of timetable scheduling and rescheduling problem. The train dispatcher can not only modify the given timetable to manage the interruptions in existing operations, but also establish schedules for additional trains. A multi-objective model minimizing both the travel time of additional trains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Genetic algorithm is a random search optimization algorithm based on evolution theory, biological selection theory, and population genetics theory [10] . It represents a computational model that imitates the natural evolution process to establish and solve problem extremum.…”
Section: Genetic Algorithm Solvingmentioning
confidence: 99%
“…Genetic algorithm is a random search optimization algorithm based on evolution theory, biological selection theory, and population genetics theory [10] . It represents a computational model that imitates the natural evolution process to establish and solve problem extremum.…”
Section: Genetic Algorithm Solvingmentioning
confidence: 99%
“…[3] A review of the scheduling system at our institute revealed the need for a feasible lecture/tutorial timetable for a department, which has been a continuous challenge in educational establishments. [5] The N Queen algorithm-based approach proved to be a useful solution; however, certain issues still need to be addressed. [7] By reviewing existing literature and proposing innovative solutions to existing problems, this work contributes to the advancement of knowledge in the field of educational scheduling.…”
Section: IImentioning
confidence: 99%
“…It is evaluated to be good if the determination of x 2 results in generating a good solution. For generating the good solution, the value of x 2 is determined by applying metaheuristics or greedy algorithms [2][3][4][5][6][7]. However, the metaheuristics are timeconsuming, and the greedy algorithms are not general-purpose.…”
Section: Basic Conceptmentioning
confidence: 99%
“…When a GA is applied to an optimization problem, especially to one with two decision variable vectors, the following strategy is often adopted [2][3][4][5][6][7]. An individual of GA is expressed by the values of one of the decision variable vectors.…”
mentioning
confidence: 99%